Exercise Medicine in the Management of Pancreatic Cancer: A Systematic Review. Issue 3 (March 2021) - Luo, Hao; Galvão, Daniel A.; Newton, Robert U.; Lopez, Pedro; Tang, Colin; Fairman, Ciaran M.; Spry, Nigel; Taaffe, Dennis R.
Abstract : Abstract: The aim of this study was to examine the health-related effects of exercise in patients with pancreatic cancer (PanCa) through a systematic review of current evidence. Studies were obtained through searching PubMed, Web of Science, PsycINFO, Embase, CINAHL Plus, and Cochrane Library databases with additional hand searches. All intervention-based studies were included if it involved (1) adult patients with PanCa, (2) exercise training, and (3) findings in quality of life, cancer-related fatigue, psychological distress, and physical function. The review protocol was registered in PROSPERO: CRD42020154684. Seven trials described in 9 publications were included consisting of 201 patients with early-stage and advanced PanCa. Participants were required to perform supervised and/or home-based, low- to moderate-intensity resistance and/or aerobic exercise for 12 to 35 weeks or duration of neoadjuvant therapy. There were no exercise-related adverse events with a reported retention rate of 71% to 90% and exercise attendance of 64% to 96%. The programs were consistently associated with improvements in cancer-related fatigue, psychological distress, and physical function, with mixed effects on quality of life. Exercise training seems to be safe and feasible and may have a beneficial effect on various physical and psychological outcomes in patients with PanCa. Further work with rigorous study designs is required to consolidate and advance current findings. Abstract : Supplemental digital content is available in the text.